Six Sigma Implementation for Chili Sauce A in PT K - Puspadewi (19015116), Deandra
The numbers of products defect to be one of the problems that almost every company faces. The product defect means it is not meeting the requirement standard. This reflects how effectively manufacturing processes and the quality of manufacturing itself are. A manufacturing process cannot be considered successful if the number of defect products exceeds the maximum limit that has been specified. This happened to PT K as a case study in this research. The number of new companies that produce chili sauce, making competition in the industry cannot be avoided. To survive in this increasingly competitive industry, quality control is important and worth to give a note. PT K as a chili sauce company that has been running long enough in it has problems in its quality control. PT K wants to reduce the number of defect products to the maximum limit in the set. The focus on this research is Chili Sauce A product which has the highest failure rate compared to other products. This research aims to identify existing problems and provide solutions that can help PT K to minimize the number of defect products, using a six sigma methodology as a tool for continuous improvement to achieve the company specification limit. This research is done through several stages such as, problem identification, data collection, literature review, observation, data analysis, conclusions, and recommendations for the company. The analysis results are used to provide solutions for companies to reduce the number of defect products and implement the given solution.